The physics and chemistry of solids - Elliott, Stephen; Elliott, S. R. ([S.l.] : Wiley, 1998)
Taking an original, imaginative approach to the subject, Stephen Elliott's book is one of the first to bridge the gap between solid state physics and chemistry. Considerable thought has gone into the structure and content of this book, with the first four chapters covering the properties of atoms in solids and the remaining four concentrating on the behaviour of electrons in materials. Fundamental principles are covered together with the very latest developments, such as combinatorial library synthesis, mesoporous materials, fullerenes and nanotubes, optical localization and the experimental observation of fractional electronic charge. Clearly written and richly illustrated, The Physics and Chemistry of Solids will be of great interest to Physicists, Chemists, Material Scientists and Engineers.
Keywords: physics,chemistry,solids